The Effect of Medication Adherence and Asthma Control in Asthma Patients at a Public Health Center in Padang, Indonesia - Dita Permatasari; Dian Ayu Juwita; Hesti Rachmawati Putri; Nurul Qalbi Desri (Fakultas Farmasi Universitas Andalas, 2022)
Asthma is characterized by reversible swelling or narrowing of the airways. Low adherence can negatively affect the effectiveness of therapy, increasing asthma morbidity and mortality. The long-term goal of asthma treatment is to achieve and maintain controlled asthma, but this goal is still challenging for most patients. This study examines the relationship between medication adherence and asthma control in patients. This study is observational, with a cross-sectional approach conducted on 40 asthma patients who received treatment at a Public Health Center. Patient medication adherence was measured by Medication Possession Ratio (MPR) method, and the level of control was measured by the Asthma Control Test (ACT) questionnaire. The results showed that most patients based on sociodemographic characteristics were female (80.0%), elderly group ≥60 years (45.0%), high school education (55.0%), and housewives (45.0%). The category of medication adherence was divided into 47.5% adherent patients and 52.5% non-adherent patients. The level of patient control was divided into fully controlled (2.50%), partly controlled (35.0%), and uncontrolled (62.5%). There was a significant relationship between adherence and asthma control (r=0.508; p<0.05). Therefore, improving patient medication adherence can potentially improve asthma control levels.